Chaoxianzu identity in literature: how novelist Jin Xuetie's work portrays Korean Chinese identity - Barone, Roberto (2025)
In China the Chaoxianzu are an ethnic minority group whose origins trace back to voluntary Korean immigration during the late 19th and early 20th centuries. This article examines the evolution of their cultural identity through a literary perspective, focusing on the work of Jin Xuetie (Kim Hak-chul), a prominent Korean Chinese novelist of the post-Maoist era. It also explores the thematic and stylistic shifts in Korean Chinese literature during the 1980s, highlighting Jin's authentic portrayal of this minority's identity within the context of contemporary Chinese society. Through his works, Jin Xuetie reflects not only on the ethnic consciousness of the Korean Chinese but also on the social contradictions that persisted in the society despite the promises of Socialism. This makes him an author who despite focusing on a specific ethnocultural group, conveys a universal message about how war and suffering shape the collective memory of a people.